تحليل المقارنة بين عملية تعليم القواعد بطريقة أمثلتي بمعهد دار الفلاح جفارا و طريقة إبتدائي بمعهد الهدى بويولالي - Zakiyyah El Miskiyyah (Rayah Al-Islam, 2021)
ملخص البحث الغرض من هذا البحث هو لتوصيف كيف عملية تعليم قواعد بطريقة أمثلتي بمعهد دار الفلاح جفارا و طريقة إبتدائي بمعهد الهدى بويولالي و يعرف المزايا و العيوب عمليتهما. أنّ المعهد خاصة المعهد السلفي هو واحدة من أماكن التعلم الديني التي لا يمكن فصلها عن تعليم القواعد. هناك طرق مختلفة تم تقديمها لاستخدامها في تعليم القواعد كوسيلة لفهمها، تلك الطرق بالتأكيد لها مزايا وعيوب. استخدمت الباحثة هذا البحث منهج الوصفية التصويرية. و المنهج المستخدمة في جمع البيانات هي منهج الملاحظة و منهج المقابلة و منهج التوثيقية. وأما تحليل البيانات في هذا البحث و يخط البحث على ثلاثة المراحل وهي تجليب البيانات, تقديم البيانات, اتخاذ الخلاصة. وأما نتائج هذا البحث هو متفرقة من شكل طريقة تعليم قواعدهما. أما عملية تعليم القواعد بطريقة أمثلتي بمعهد دار الفلاح جفارا تدخل في طريقة قياسية. و أما عملية تعليم القواعد بطريقة إبتدائي بمعهد الهدى بويولالي تدخل في طريقة إستقرائية. Abstract The purpose of this study was to explain how the qowaid learning process with the Amtsilati method at the Darul Falah Islamic Boarding School in Jepara and the Ibtidai method at the Al-Huda Boyolali Islamic Boarding School. And know the advantages and disadvantages of both processes. Islamic boarding schools, especially Salaf-based Islamic boarding schools, are one of the places for religious learning that cannot be separated from grammar learning. Various methods are presented for use in learning grammar as a way to understand it, these methods certainly have advantages and disadvantages.Researchers used descriptive research and the methods used in collecting data were observation, interviews, and documentation. And data analysis in this study with three steps, namely by taking data, presenting data, and making conclusions. The results in this study are the differences seen from the direction of the qowaid method. The qowaid learning process using the Amtsilati method at the Darul Falah Islamic Boarding School in Jepara is included in the Qiyasiyah method. And the qowaid learning process using the Ibtida'i method at the Al-Huda Boyolali Islamic boarding school is included in the Istiqroiyyah method.